Efficacy of protaper instruments during endodontic retreatment - Luiz Fernando Fariniuk; Marco Antonio Diniz Azevedo; Everdan Carneiro; Vânia Portela Ditzel Westphalen; Lucila Piasecki; Ulisses Xavier da Silva Neto (Wolters Kluwer Medknow Publications, 2017)
Introduction: The effectiveness of ProTaper Universal and ProTaper Retreatment rotary instruments was compared to the Hedström files in the removal of filling material from root canals. Materials and Methods: Thirty-six extracted human mandibular premolars with a single straight root canal were shaped and filled with gutta-percha and AH Plus. The specimens were stored for 6 months at 37°C and at 100% relative humidity, and then randomly divided into three groups: PTU - removal of filling material performed with ProTaper Universal instruments; PTR - removal of filling material performed with ProTaper Retreatment instruments; HF - removal of filling material performed with Gates-Glidden burs, Hedström files and solvent. After the filling material removal and diaphanization, the specimens were longitudinally sectioned and images of the canal surfaces were scanned. The remaining areas of filling material were measured (Image Tool 3.0), and data was analyzed statistically (Kruskal-Wallis and Dunn tests). The time required for filling removal in each group was also recorded (one-way ANOVA and Tukey's HSD test). Results: All groups presented remnants of filling material; PTU had the smallest amount and HF group presented the highest mean value (P< 0.05) in all the thirds. The cervical third had the smallest amount of material when compared with the other thirds (P< 0.05). HF group required a longer mean time, presenting significant difference (P< 0.05). Conclusion: Considering the time required and the amount of the filling removal, ProTaper Retreatment were not superior to ProTaper Universal, but both rotary instruments were more effective and less time-consuming than Hedström manual files.